2012
DOI: 10.3109/02699052.2011.648707
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life after traumatic brain injury: A 2-year follow-up study in Wuhan, China

Abstract: HRQoL of a group of Chinese patients with TBI improved during 2 years after discharge. Age, sex and severity of TBI were significantly associated with physical or mental HRQoL after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
3
20
2
1
Order By: Relevance
“…All SF-36 domain scores for all 3 TBI severities increased over time, suggesting improvement on the whole spectrum of HRQL after mild, moderate and severe TBI. However, comparison of SF-36 outcome at one year follow-up with Dutch population norms [39] revealed outcomes in line with studies in which HRQL was lower for TBI patients than for the general population [2,[11][12][13]. This study used Dutch population norms, which vary from US population norms [40].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…All SF-36 domain scores for all 3 TBI severities increased over time, suggesting improvement on the whole spectrum of HRQL after mild, moderate and severe TBI. However, comparison of SF-36 outcome at one year follow-up with Dutch population norms [39] revealed outcomes in line with studies in which HRQL was lower for TBI patients than for the general population [2,[11][12][13]. This study used Dutch population norms, which vary from US population norms [40].…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to the GOSE, HRQL measures enable comparison of health outcome after TBI with other diseases and the general population, and their outcome in terms of an health status on a scale from 0 (death) to 1 (perfect health) scale can be used in economic evaluations. Research has shown that even years after injury, many TBI patients still report significantly lower HRQL than the general population [1,2,[11][12][13][14]. Most studies however, focus on recovery after mild [15][16][17] or moderate and severe [1,12,13,18,19] TBI.…”
mentioning
confidence: 99%
“…Our estimate of decrease in the physical component was more pronounced than reported in the study by Villanueva et al Perhaps this was because the Villanueva et al studied university graduates who might have been more likely than the general population to adopt effective coping mechanism and able to seek care. In addition, the time lag after the injuries in the Villaneueva et al study was up to 4 years, which could have resulted in patients regaining some of the lost HRQOL after the injury [18, 34]. In our data, those injured in the earlier round (3) did exhibit less magnitude in HRQOL deficit than those injured at round 4, supporting the fact that injured individuals regain some lost quality of life.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, there is an extensive literature on the effects on HRQOL of other chronic and acute health conditions [5, 13, 14, 3032, 3638, 40]. While a number of studies have looked at HRQOL following injuries, these studies lack methodological rigor and few focus specifically on automobile-related injuries [6, 1520, 3234]. …”
Section: Introductionmentioning
confidence: 99%
“…Se han estudiado en profundidad las variables que influyen en la mejora de la CVRS tras un DCA, encontrando determinantes la severidad de la lesión (Hu, Feng, Fan, Xiong, y Huang, 2012;Ilmer et al, 2016), los costes económicos (Lopez-Bastida et al, 2012;Mar et al, 2011), la capacidad funcional (movilidad) (C. Chen et al, 2015;Gillard et al, 2015;Hong, 2015;Mar et al, 2011;Min y Min, 2015;Walsh, Galvin, Loughnane, Macey, y Horgan, 2014;Williamson et al, 2013), los síntomas depresivos y el estado de ánimo (Arango-Lasprilla, Krch, Drew, De Los Reyes Aragon, y Stevens, 2012; Boosman et al, 2015;Di Battista, Godfrey, Soo, Catroppa, y Anderson, 2014;Grauwmeijer, Heijenbrok-Kal, y Ribbers, 2014;Haagsma et al, 2015;Walsh et al, 2014;Williamson et al, 2013), el nivel cognitivo (Arango-Lasprilla et al, 2012;Boosman et al, 2015;C. Chen et al, 2015;Sasse et al, 2013), el grado de participación en las actividades (C. Chen et al, 2015;Chou, 2015;Faulkner et al, 2015) y el soporte social (Arango-Lasprilla et al, 2012).…”
Section: Calidad De Vida En Relación a La Saludunclassified